Advances in social and organizational factors - Vink, P. (Boca Raton, Fla. : CRC Press, 2012)
"Preface The National Academy of Engineering Committee on Engineering's Grand Challenges has identified in 2008 14 areas awaiting engineering solutions in the 21st century (see http://www.engineeringchallenges.org/cms/8996.aspx). These 14 areas were defined by a panel of technology and engineering luminaries. The goal of the panel was to create a slate of Grand Challenges for scientists and engineers. Among these challenges five are directly related to the content of this book: 1. Restore and improve urban infrastructure 2. Advance health informatics 3. Prevent terror 4. Improve cyberspace 5. Advanced personalized learning This means that the contributions in this book are of a high value for the future of the world. These challenges have a more technological point of view as they are defined from an engineering perspective. The Lund Declaration prepared the future European Grand Societal Challenges (Chuberre & Lioli, 2010). So, these are more focused on societal issues. They identified six themes calling for solutions to tackle them. Two of these are closely related to the content of this book: 6. Ageing societies: As the life duration of people increases, this raises numerous issues among which economic, social inclusion and accessibility. 7. Security: How to improve the security of European citizens and their goods within but also outside Europe? "--
section 1. Perception and design of spaces -- section 2. Ergonomics in industrial quality -- section 3. Human factotrs [sic] in terrorism -- section 4. Enterprise ICT and work -- section 5. Learning and training -- section 6. Flexible work force and work schedule -- section 7. Adapting for special groups -- section 8. Ship design -- section 9. Changes at the organizational level -- section 10. New ways of work -- section 11. User experience, comfort and emotion.
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Technology -- Social aspects; Technological innovations; Electronic books